Nitric oxide negatively regulates gibberellin signaling to coordinate growth and salt tolerance in Arabidopsis. (August 2022) - Chen, Lichao; Sun, Shuhao; Song, Chun-Peng; Zhou, Jian-Min; Li, Jiayang; Zuo, Jianru
Abstract: In response to dynamically altered environments, plants must finely coordinate the balance between growth and stress responses for their survival. However, the underpinning regulatory mechanisms remain largely elusive. The phytohormone gibberellin promotes growth via a derepression mechanism by proteasomal degradation of the DELLA transcription repressors. Conversely, the stress-induced burst of nitric oxide (NO) enhances stress tolerance, largely relying on NO-mediated S -nitrosylation, a redox-based posttranslational modification. Here, we show that S -nitrosylation of Cys-374 in the Arabidopsis RGA protein, a key member of DELLAs, inhibits its interaction with the F-box protein SLY1, thereby preventing its proteasomal degradation under salinity condition. The accumulation of RGA consequently retards growth but enhances salt tolerance. We propose that NO negatively regulates gibberellin signaling via S -nitrosylation of RGA to coordinate the balance of growth and stress responses when challenged by adverse environments.